Speed training in difficult and easier conditions - Bajramovic, I.; Likic, S.; Mekic, A.; Vranesic-Hadzimehmedovic, D. (Sport Science - International Scientific Journal of Kinesiology, 2015)
Different biological, motor, energy, cognitive and other factors affect the quality of speed manifestation. Speed in the form of sprint is one of the most important motor skills. It defines success in many sports situations. Speed training in difficult conditions refers to increased stress during sprint, while speed training in the easier conditions refers to assistance when performing sprint exercises. The effects of these specific training are: higher frequency and stride length. During the speed training in difficult to easier conditions, it is very important to determine the level of resistance and speed of performing an exercise in relation to competitive activity. These specific loads should not disturb coordination. It is very important to integrate the benefits of speed training in specific movement structures of a certain sport. Training in difficult and easier conditions is intended for well-trained athletes.